The Application Of Cooperative Learning Model Of Team Assisted Individualization (TAI) Based Manipulative Media On Topics “Shape” Of Class VI Elementary School Of Tombolok Gowa - Aqsyari Pujianti Syam; Irwan Akib; Agustan Syamsuddin (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2019)
This study aims to describe the application of the cooperative learning model of the Team Assisted Individualization (TAI) type assisted by manipulative learning media to improve student learning outcomes in shape material. This study involved 29 elementary grade VI students as a research sample and used a pre-experimental research type with a one-group pretest-posttest design. Student mathematics learning outcomes data obtained from student learning outcomes tests consisting of 10 breakdown questions and analyzed using descriptive and inferential analysis. To see an increase in student mathematics learning outcomes can be interpreted using normalized gain (N-gain). From the results of data analysis, it is obtained that: (1) the average value of student learning outcomes before applying the TAI learning model assisted by manipulative media is 42.21 with a low category; (2) the average value of learning outcomes after applying the TAI learning model assisted by manipulative media is 74.76 with a high category; (3) hypothesis test results obtained tcount> t table (13,589> 2,048) and the significance value is 0,000 <0.05 so that Ha (Ha: µ1 <µ2) is accepted; (4) increase in the value of pretest and posttest with gain index (d) of 0.56 with the medium category. Thus, it can be concluded that the application of the cooperative learning model of the TAI type can improve the learning outcomes of elementary school students in grade VI in shape material. Therefore, this type of TAI cooperative learning model can be used as an alternative learning model that can be used in order to improve student learning outcomes